The Standardized Data Management Plan for Educational Research - Sebastian Netscher; Harald Kaluza; Reiner Mauer; Kati Mozygemba; Karsten Stephan (International Journal of Digital Curation)
Although there is an increasing number of tools and support opportunities, research data management is still challenging. Conventional templates of data management plans (DMP) guide users, but hardly support them in implementing and realizing data management. Instead, users of conventional templates require more tailored guidance to better understand how to manage their data according to the needs of their research discipline, and its methods and practises, e.g., regarding data sharing. To provide more tailored, discipline-specific guidance, Science Europe (2018) suggests developing and using so-called Domain Data Protocols, i.e., a model DMP for a given discipline or community. The project Domain Data Protocols for Empirical Educational Research was one of the first to turn this concept into a practically useable DMP template tailored to educational research by developing the Standardised Data Management Plan for Educational Research (Stamp). The Stamp is designed to assist researchers in managing their data, appropriately, and to ensure shareable data according to the FAIR Data Principles. Due to its flexible structure, its checklist and auxiliary materials, the Stamp tackles most of the challenges of conventional DMP templates. Providing tailored, discipline-specific guidance and enabling to manage various types of data, the Stamp is an innovative approach to further professionalize data management.